2017
DOI: 10.1080/24732850.2017.1317560
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Change in Dynamic Factors Using the START: AV

Abstract: Historical approaches to violence risk assessment emphasized prediction of future violence and focused on static or historical risk factors. Consideration of dynamic factors as part of a comprehensive violence risk assessment approach may allow practitioners to better tailor treatment and risk management strategies. Limited research exists on whether risk assessment instruments can detect change in dynamic factors over time. The Short-Term Assessment of Risk and Treatability: Adolescent Version (START:AV) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Another unique feature is the tool's balanced approach to risk and protective factors, which corresponds with the setting's philosophy to observe, validate and strengthen the assets of a youth. Moreover, because of its dynamic nature, the instrument can detect reliable change over short time periods, which is in line with the setting's treatment cycle of 4 months (Sellers, Desmarais, & Hanger, 2017). The START:AV forms and user guide were officially translated into Dutch (De Beuf, de Ruiter, & de Vogel, 2016), with permission from and in consultation with the original authors.…”
Section: Settingmentioning
confidence: 97%
“…Another unique feature is the tool's balanced approach to risk and protective factors, which corresponds with the setting's philosophy to observe, validate and strengthen the assets of a youth. Moreover, because of its dynamic nature, the instrument can detect reliable change over short time periods, which is in line with the setting's treatment cycle of 4 months (Sellers, Desmarais, & Hanger, 2017). The START:AV forms and user guide were officially translated into Dutch (De Beuf, de Ruiter, & de Vogel, 2016), with permission from and in consultation with the original authors.…”
Section: Settingmentioning
confidence: 97%
“…Still, 10% of the START: AV forms fell above the cutoff for missing item rationales (i.e., more than 20%). This cutoff is based on a benchmark for missing items used in risk assessment research (Sellers et al, 2017). With respect to providing a rationale for the risk estimates, only one in five forms included appropriate arguments for all adverse outcomes rated as moderate or high risk (STARS 9: "Risk Estimate Rationale").…”
Section: Adherence To the Start:av Featuresmentioning
confidence: 99%
“…38 For these reasons, risk assessments will have a shelf life. Although research has demonstrated that dynamic factors do change over time, 81,82 there is limited evidence regarding the optimal period of time for reassessment and review. 24 In practice, optimal periods for review and reassessment may differ per person as function of their case characteristics, current functioning, and circumstances.…”
Section: Informing Decisionsmentioning
confidence: 99%